Bi-interface induced multi-active MCo2O4@MCo2S4@PPy (M=Ni, Zn) sandwich structure for energy storage and electrocatalysis. (March 2019) - Zhao, Depeng; Liu, Henqi; Wu, Xiang
Abstract: Rational interface tailoring of nanomaterials is a significant and efficient strategy to develop the desired electrode materials for energy storage and electrocatalysts for OER. In this work, the MCo2 O4 @MCo2 S4 @PPy sandwich structures are prepared through a simple solution approach. The as-synthesized products can be utilized directly for the electrode materials of hybrid capacitor, which delivers a specific capacitance of 835.2 C g −1 at 1 A g −1 and a retention rate of 90.07% after 10000 cycles, revealing that bi-interface of the product can motivate more active sites than single interface. Moreover, the sandwich structured product also exhibit low overpotential of 298 mV at 50 mA cm −2 and 395 mV at current density of 100 mA cm −2 . In this work, the MCo2 O4 @MCo2 S4 @PPy sandwich structures are prepared through a facile solution route. The as-synthesized products can be used directly as the electrode materials for hybrid capacitor and electrocatalyst. Graphical abstract: fx1 Highlights: The MCo2 O4 @MCo2 S4 @PPy sandwich structures are prepared through a facile solution route. The as-synthesized products can be used directly as the electrode materials for hybrid capacitor with high capacitance. The sandwich structured product exhibit low overpotential of 228 mV at 50 mA cm −2 .